RuO2 / ZnO / Ru / Zn porous carbon material derived from ZIFs material as well as preparation and application of RuO2 / ZnO / Ru / Zn porous carbon material
By impregnating Ru on the surface of ZIF-8 and calcining, the RuO2/ZnO/Ru/Zn porous carbon material is obtained, and the problems of high cost and insufficient performance of the electrolytic oxygen evolution reaction and chlorine evolution reaction catalyst in the prior art are solved, thereby achieving efficient electrocatalytic performance and cost reduction.
Patent Information
- Application Number
- CN202411700084.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-04-08
AI Technical Summary
The high cost and insufficient performance of catalysts in electrolytic oxygen evolution reactions (OER) and chlorine evolution reactions limit the large-scale industrial application of these reactions.
Ru was adsorbed on the surface of ZIF-8 by impregnation method, and a catalytic site was provided for Ru by using the high specific surface area porous structure of ZIF-8, and RuO2/ZnO/Ru/Zn porous carbon material was obtained by calcination.
The material exhibits excellent electrocatalytic properties, improves the catalytic activity of electrolytic oxygen evolution reaction and chlorine evolution reaction, and reduces the cost of the catalyst.
Smart Images

Figure CN119776901A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst materials and relates to a RuO2 / ZnO / Ru / Zn porous carbon material derived from a ZIFs material and a preparation method and application thereof. Background Art
[0002] In today's society, the greenhouse effect has produced a series of hazards and has had an immeasurable impact on global climate change. In order to curb the greenhouse effect caused by the burning of fossil fuels, it is urgent to develop clean renewable energy. Hydrogen energy, as a green energy, has attracted much attention. Among the many hydrogen production methods, water electrolysis is an important means to achieve the dual carbon goals by coupling renewable energy generation with water electrolysis to produce hydrogen under the premise of meeting low-carbon emissions. The water electrolysis reaction includes the cathode hydrogen evolution reaction (HER) and the anode oxygen evolution reaction (OER). Compared with the cathode hydrogen evolution reaction, the reaction kinetics of the anode oxygen evolution reaction (OER) is much slower, involving a slow four-electron transfer process of adsorption, deprotonation, coupling and desorption. Therefore, the development of low-cost, long-term stable deoxygenation reaction (OER) catalysts is a top priority to increase the OER reaction rate, but the technology still faces challenges. On the other hand, electrolytic chlorine production technology is widely used in the chlor-alkali industry, seawater decontamination and water treatment, and the anode where the chlorine evolution reaction (CER) occurs is the key to this technology, but it strongly relies on the use of dimensionally stable anodes (DSA) on titanium substrates and a large amount of precious Ru / Ir oxides. Therefore, the high cost seriously limits the large-scale industrial application of OER and CER. For the purpose of sustainable development, the reduction of precious metals and the improvement of performance are urgent needs for the development of OER and CER anodes.
[0003] For example, Chinese patent application CN202111415299.3 provides a graphene oxide-coated ZIF-67-derived iron / cobalt / nitrogen / co-doped porous carbon nanoparticle composite material. The present invention adsorbs Ru on the surface of ZIF-8 by an impregnation method, and the unique high specific surface area porous structure of ZIF-8 provides sufficient catalytic sites for the active center Ru. The RuO2 / ZnO / Ru / Zn porous carbon material obtained by subsequent calcination exhibits excellent electrocatalytic performance. Summary of the invention
[0004] The purpose of the present invention is to provide a RuO2 / ZnO / Ru / Zn porous carbon material derived from a ZIFs material and its preparation and application, so as to improve the catalytic activity in the oxygen evolution reaction (OER) and chlorine evolution reaction in water electrolysis.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] In one aspect, the present invention provides a method for preparing a RuO2 / ZnO / Ru / Zn porous carbon material derived from a ZIFs material, comprising the following steps:
[0007] (1) slowly adding C4H6O4Zn·2H2O methanol solution into 2-methylimidazole methanol solution, stirring at room temperature until a milky white solution is formed, placing in a high pressure hydrothermal reactor for reaction, and then cooling to room temperature;
[0008] (2) adding RuCl3·xH2O to the reaction solution cooled in step (1), stirring and mixing to obtain a brown solution, immersing, and drying;
[0009] (3) placing the dried product obtained in step (2) under an inert atmosphere, heating it for carbonization, and cooling it to obtain Ru / Zn porous carbon;
[0010] (4) Oxidizing the Ru / Zn porous carbon in an air atmosphere to obtain RuO2 / ZnO / Ru / Zn porous carbon material, which is the target product.
[0011] Furthermore, in step (1), the molar ratio of 2-methylimidazole to C4H6O4Zn·2H2O is 2-8:1.
[0012] Furthermore, in step (1), the reaction temperature is 110-130° C., the reaction time is 4-12 h, and the reaction pressure is 3-8 MPa.
[0013] Furthermore, in step (2), the addition amount of RuCl3·xH2O and C4H6O4Zn·2H2O satisfies n Zn :n Ru =3.8~7.7:1.
[0014] Furthermore, in step (2), the immersion is carried out at room temperature for 18-30 hours.
[0015] Furthermore, in step (3), the specific process of heating carbonization is: controlling the heating rate to 2-5°C / min, heating to 800-1000°C, and keeping the temperature for 2-3 hours.
[0016] Furthermore, the inert atmosphere is an argon atmosphere.
[0017] Furthermore, in step (4), the specific process of oxidation is: controlling the heating rate to be 2-5°C / min, heating to 450-500°C, and keeping the temperature for 4-6 hours.
[0018] Furthermore, in step (2), the drying temperature is 80° C. and the drying time is 12 h.
[0019] In a second aspect, the present invention provides a RuO2 / ZnO / Ru / Zn porous carbon material derived from a ZIFs material, which is prepared by any of the preparation methods described above. In the present invention, Ru is adsorbed on the surface of ZIF-8 by an impregnation method, and the unique high specific surface area porous structure of ZIF-8 provides sufficient catalytic sites for the active center Ru. The RuO2 / ZnO / Ru / Zn porous carbon material obtained by subsequent calcination exhibits excellent electrocatalytic performance.
[0020] In a third aspect, the present invention provides a RuO2 / ZnO / Ru / Zn porous carbon material derived from a ZIFs material for use as a catalyst for hydrogen production from water electrolysis, a hydrogen storage material, and a chlorine evolution reaction catalyst. Specifically, the porous material can be used as an oxygen evolution reaction (OER) catalyst for water electrolysis. The porous carbon material of the present invention is beneficial for increasing the active sites of the catalyst and improving the stability, and can be used in oxygen evolution reaction from water electrolysis and chlorine evolution reaction in the chlor-alkali industry.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] (1) During the high-temperature calcination process, ZIF-8 first decomposes into carbon-based materials and ZnO. At about 750°C, ZnO is reduced to Zn by the carbon-based materials. At about 900°C, Zn is evaporated, leaving a large number of pores, which gives it a high specific surface area and becomes a porous carbon material. The Ru element is anchored by the carbonized porous carbon to form a stable active site. Therefore, the method of effectively increasing the specific surface area and active sites of carbon materials by utilizing the porous carbon structure obtained by calcining ZIF-8 crystals is universal and reliable.
[0023] (2) The prepared RuO2 / ZnO / Ru / Zn porous carbon material catalyst, in which the evaporation of Zn atoms leaves a large number of pores and uniformly dispersed Ru active sites in the carbon matrix, can comprehensively improve its catalytic performance in water electrolysis and chlorine evolution reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a scanning electron microscope (SEM) image of RuO2 / ZnO / Ru / Zn porous carbon material;
[0025] Figure 2 This is the electrochemical performance diagram of the oxygen evolution reaction (OER) of RuO2 / ZnO / Ru / Zn porous carbon material. DETAILED DESCRIPTION
[0026] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0027] In the following examples, unless otherwise specified, raw materials, reagents or processing techniques are all conventional commercial products or conventional processing techniques in the art.
[0028] Example 1
[0029] (1) To prepare ZIF-8 solution, 4.204 g 2-methylimidazole and 1.372 g C4H6O4Zn·2H2O (molar ratio of 4:1) were weighed and dissolved in 30 mL methanol, and magnetic stirring was performed to obtain a fully dissolved solution; the C4H6O4Zn·2H2O methanol solution was slowly added to the 2-methylimidazole methanol solution, and magnetic stirring was performed for 2 h at room temperature until a milky white solution was obtained.
[0030] (2) Hydrothermal preparation of ZIF-8 precursor solution: Pour the milky white solution obtained at room temperature into a polytetrafluoroethylene liner, place it in a high-pressure hydrothermal reactor, heat it to 120°C in an oven, and keep it warm for 4 hours. The reaction pressure is about 5 MPa.
[0031] (3) Precursor impregnation: Add 133 mg of RuCl3·xH2O (satisfying n Zn :n Ru =3.8:1) magnetic stirring for 0.5h, the brown solution was placed in a beaker and stirred thoroughly, then immersed at room temperature for 24h; and the mixed solution was placed in a vacuum oven and dried for 12h.
[0032] (4) Calcination: The crucible containing the dried precursor was placed in a tubular quartz furnace, heated to 800°C at a heating rate of 5°C / min in an argon atmosphere of 80 mL / min, kept at this temperature for 2 h, and then naturally cooled to room temperature to obtain a Ru / Zn porous carbon material.
[0033] (5) The Ru / Zn porous carbon product was transferred into a muffle furnace, heated to 450°C at a heating rate of 5°C / min, kept at this temperature for 5 h, and then naturally cooled to room temperature to obtain the target RuO2 / ZnO / Ru / Zn porous carbon product.
[0034] (6) OER electrocatalytic performance test: The electrochemical performance test of RuO2 / ZnO / Ru / Zn porous carbon materials was carried out in 1M potassium hydroxide electrolyte at a scan rate of 10 mV / s, with RHE as the reference electrode and an electrochemical window scanning range of 1.2-1.8 V. -2 The corresponding overpotential is about 270mV.
[0035] (7) The prepared RuO2 / ZnO / Ru / Zn porous carbon material was used to test the chlorine evolution performance of the chlor-alkali electrolytic cell: the RuO2 / ZnO / Ru / Zn porous carbon material was used as the anode material of the chlor-alkali electrolytic cell, the reference electrode was a calomel electrode of a saturated potassium chloride solution, a polytetrafluoroethylene tube salt bridge, and the experimental electrolyte was a 5.13M NaCl solution. Under the constant DC input state, the experimental operating current density was 2 kA / m 2 , experimental temperature 25±2℃. After the electrolysis reaction for 10 minutes, read the instantaneous minimum value of the potential within 20 seconds, which is the chlorine evolution potential of the electrode sheet. The chlorine evolution potential of the electrode sheet in this embodiment: 10mA cm -2 The corresponding overpotential is about 190mV.
[0036] Example 2
[0037] (1) To prepare ZIF-8 solution, 4.204 g 2-methylimidazole and 1.372 g C4H6O4Zn·2H2O (molar ratio of 4:1) were weighed and dissolved in 30 mL methanol, and magnetic stirring was performed to obtain a fully dissolved solution; the C4H6O4Zn·2H2O methanol solution was slowly added to the 2-methylimidazole methanol solution, and magnetic stirring was performed for 2 h at room temperature until a milky white solution was obtained.
[0038] (2) Hydrothermal preparation of ZIF-8 precursor solution: Pour the milky white solution obtained at room temperature into a polytetrafluoroethylene liner, place it in a high-pressure hydrothermal reactor, heat it to 120°C in an oven, and keep it warm for 4 h;
[0039] (3) Precursor impregnation: Add 133 mg of RuCl3·xH2O (n Zn :n Ru =3.8:1) magnetic stirring for 0.5h, the brown solution was placed in a beaker and stirred thoroughly, then immersed at room temperature for 24h; and the mixed solution was placed in a vacuum oven and dried for 12h.
[0040] (4) Calcination: The crucible containing the dried precursor was placed in a tubular quartz furnace, heated to 900°C at a heating rate of 5°C / min in an argon atmosphere of 80 mL / min, kept at this temperature for 2 h, and then naturally cooled to room temperature to obtain a Ru / Zn porous carbon material.
[0041] (5) The product Ru / Zn@NC was transferred into a muffle furnace, heated to 450°C at a heating rate of 5°C / min, kept at this temperature for 5 h, and then naturally cooled to room temperature to obtain the target product of RuO2 / ZnO / Ru / Zn porous carbon.
[0042] (6) OER electrocatalytic performance test: The electrochemical performance test of RuO2 / ZnO / Ru / Zn porous carbon materials was carried out in 1M potassium hydroxide electrolyte at a scan rate of 10 mV / s, with RHE as the reference electrode and an electrochemical window scanning range of 1.2-1.8 V. -2 The corresponding overpotential is about 260mV.
[0043] (7) The prepared RuO2 / ZnO / Ru / Zn porous carbon material was used to test the chlorine evolution performance of the chlor-alkali electrolytic cell: the RuO2 / ZnO / Ru / Zn porous carbon material was used as the anode material of the chlor-alkali electrolytic cell, the reference electrode was a calomel electrode of a saturated potassium chloride solution, a polytetrafluoroethylene tube salt bridge, and the experimental electrolyte was a 5.13M NaCl solution. Under the constant DC input state, the experimental operating current density was 2 kA / m 2 , experimental temperature 25±2℃. After the electrolysis reaction for 10 minutes, read the instantaneous minimum value of the potential within 20 seconds, which is the chlorine evolution potential of the electrode sheet. The chlorine evolution potential of the electrode sheet in this embodiment: 10mA cm -2 The corresponding overpotential is about 170mV.
[0044] Example 3
[0045] (1) To prepare ZIF-8 solution, 4.204 g 2-methylimidazole and 1.372 g C4H6O4Zn·2H2O (molar ratio of 4:1) were weighed and dissolved in 30 mL methanol, and magnetic stirring was performed to obtain a fully dissolved solution; the C4H6O4Zn·2H2O methanol solution was slowly added to the 2-methylimidazole methanol solution, and magnetic stirring was performed for 2 h at room temperature until a milky white solution was obtained.
[0046] (2) Hydrothermal preparation of ZIF-8 precursor solution: Pour the milky white solution obtained at room temperature into a polytetrafluoroethylene liner, place it in a high-pressure hydrothermal reactor, heat it to 120°C in an oven, and keep it warm for 4 h;
[0047] (3) Precursor impregnation: Add 260 mg of RuCl3·xH2O (n Zn :n Ru =7.7:1) magnetically stirred for 0.5 h, the brown solution was placed in a beaker and stirred thoroughly, then immersed at room temperature for 24 h; and the mixed solution was placed in a vacuum oven and dried for 12 h.
[0048] (4) Calcination: The crucible containing the dried precursor was placed in a tubular quartz furnace, heated to 900°C at a heating rate of 5°C / min in an argon atmosphere of 80 mL / min, kept at this temperature for 2 h, and then naturally cooled to room temperature to obtain a Ru / Zn porous carbon material.
[0049] (5) The Ru / Zn porous carbon product was transferred into a muffle furnace, heated to 450°C at a heating rate of 5°C / min, kept at this temperature for 5 h, and then naturally cooled to room temperature to obtain the target RuO2 / ZnO / Ru / Zn porous carbon product.
[0050] (6) OER electrocatalytic performance test: The electrochemical performance test of RuO2 / ZnO / Ru / Zn porous carbon materials was carried out in 1M potassium hydroxide electrolyte at a scan rate of 10 mV / s, with RHE as the reference electrode and an electrochemical window scanning range of 1.2-1.8 V. -2 The corresponding overpotential is 253 mV.
[0051] (7) The prepared RuO2 / ZnO / Ru / Zn porous carbon material was used to test the chlorine evolution performance of the chlor-alkali electrolytic cell: the RuO2 / ZnO / Ru / Zn porous carbon material was used as the anode material of the chlor-alkali electrolytic cell, the reference electrode was a calomel electrode of a saturated potassium chloride solution, a polytetrafluoroethylene tube salt bridge, and the experimental electrolyte was a 5.13M NaCl solution. Under the constant DC input state, the experimental operating current density was 2 kA / m 2 , experimental temperature 25±2℃. After the electrolysis reaction for 10 minutes, read the instantaneous minimum value of the potential within 20 seconds, which is the chlorine evolution potential of the electrode sheet. The chlorine evolution potential of the electrode sheet in this embodiment: 10mA cm -2 The corresponding overpotential is about 135 mV, showing good electrochemical performance.
[0052] Example 4
[0053] (1) To prepare ZIF-8 solution, 4.204 g 2-methylimidazole and 1.372 g C4H6O4Zn·2H2O (molar ratio of 2:1) were weighed and dissolved in 30 mL methanol respectively, and magnetic stirring was performed to obtain a fully dissolved solution; the C4H6O4Zn·2H2O methanol solution was slowly added to the 2-methylimidazole methanol solution, and magnetic stirring was performed for 2 h at room temperature until a milky white solution was obtained.
[0054] (2) Hydrothermal preparation of ZIF-8 precursor solution: Pour the milky white solution obtained at room temperature into a polytetrafluoroethylene liner, place it in a high-pressure hydrothermal reactor, heat it to 120°C in an oven, and keep it warm for 4 h;
[0055] (3) Precursor impregnation: Add 133 mg of RuCl3·xH2O (n Zn :n Ru =3.8:1) magnetic stirring for 0.5h, the brown solution was placed in a beaker and stirred thoroughly, then immersed at room temperature for 24h; and the mixed solution was placed in a vacuum oven and dried for 12h.
[0056] (4) Calcination: The crucible containing the dried precursor was placed in a tubular quartz furnace, heated to 1000°C at a heating rate of 5°C / min in an argon atmosphere of 80 mL / min, kept warm for 2 h, and then naturally cooled to room temperature to obtain a Ru / Zn porous carbon material.
[0057] (5) The Ru / Zn porous carbon product was transferred into a muffle furnace, heated to 450°C at a heating rate of 5°C / min, kept at this temperature for 5 h, and then naturally cooled to room temperature to obtain the target RuO2 / ZnO / Ru / Zn porous carbon product.
[0058] (6) OER electrocatalytic performance test: The electrochemical performance test of RuO2 / ZnO / Ru / Zn porous carbon materials was carried out in 1M potassium hydroxide electrolyte at a scan rate of 10 mV / s, with RHE as the reference electrode and an electrochemical window scanning range of 1.2-1.8 V. -2 The corresponding overpotential is about 300mV.
[0059] Comparative Example 1:
[0060] Compared with Example 3, most of the details are the same except for the addition amount of RuCl3·xH2O.
[0061] (1) To prepare ZIF-8 solution, 4.204 g 2-methylimidazole and 1.372 g C4H6O4Zn·2H2O (molar ratio of 4:1) were weighed and dissolved in 30 mL methanol, and magnetic stirring was performed to obtain a fully dissolved solution; the C4H6O4Zn·2H2O methanol solution was slowly added to the 2-methylimidazole methanol solution, and magnetic stirring was performed for 2 h at room temperature until a milky white solution was obtained.
[0062] (2) Hydrothermal preparation of ZIF-8 precursor: The milky white solution obtained at room temperature was poured into a polytetrafluoroethylene liner, placed in a high-pressure hydrothermal reactor, heated to 120°C in an oven, kept warm for 4 h, cooled to room temperature, filtered, washed with methanol three times, and the solid product was collected and placed in a vacuum oven at 30°C for 12 h to remove excess methanol solution to obtain a ZIF-8 precursor.
[0063] (3) Precursor impregnation: Add 133 mg of RuCl3·xH2O (n Zn :n Ru =3.8:1) magnetic stirring for 0.5h, the brown solution was placed in a beaker and stirred thoroughly, then immersed at room temperature for 24h; and the mixed solution was placed in a vacuum oven and dried for 12h.
[0064] (4) Calcination: The crucible containing the dried precursor was placed in a tubular quartz furnace, heated to 900°C at a heating rate of 5°C / min in an argon atmosphere of 80 mL / min, kept at this temperature for 2 h, and then naturally cooled to room temperature to obtain a Ru / Zn porous carbon material.
[0065] (5) The Ru / Zn porous carbon product was transferred into a muffle furnace, heated to 450°C at a heating rate of 5°C / min, kept at this temperature for 5 h, and then naturally cooled to room temperature to obtain the target RuO2 / ZnO / Ru / Zn porous carbon product.
[0066] (6) OER electrocatalytic performance test: The electrochemical performance test of RuO2 / ZnO / Ru / Zn porous carbon materials was carried out in 1M potassium hydroxide electrolyte at a scan rate of 10 mV / s, with RHE as the reference electrode and an electrochemical window scanning range of 1.2-1.8 V. -2 The corresponding overpotential is about 281 mV. Compared with Example 3, the sample calcined at 900°C in a tube furnace (10 mA cm -2 The corresponding overpotential is 253 mV), showing poor electrochemical performance.
[0067] Comparative Example 2:
[0068] Compared with Example 3, most of the details are the same except for the calcination temperature.
[0069] (1) To prepare ZIF-8 solution, 4.204 g 2-methylimidazole and 1.372 g C4H6O4Zn·2H2O (molar ratio of 4:1) were weighed and dissolved in 30 mL methanol, and magnetic stirring was performed to obtain a fully dissolved solution; the C4H6O4Zn·2H2O methanol solution was slowly added to the 2-methylimidazole methanol solution, and magnetic stirring was performed for 2 h at room temperature until a milky white solution was obtained.
[0070] (2) Hydrothermal preparation of ZIF-8 precursor solution: Pour the milky white solution obtained at room temperature into a polytetrafluoroethylene liner, place it in a high-pressure hydrothermal reactor, heat it to 120°C in an oven, and keep it warm for 4 h;
[0071] (3) Precursor impregnation: Add 260 mg of RuCl3·xH2O (n Zn :n Ru =7.7:1) magnetically stirred for 0.5 h, the brown solution was placed in a beaker and stirred thoroughly, then immersed at room temperature for 24 h; and the mixed solution was placed in a vacuum oven and dried for 12 h.
[0072] (4) Calcination: The crucible containing the dried precursor was placed in a tubular quartz furnace and heated to 800°C and 1000°C, respectively, at a heating rate of 5°C / min in an argon atmosphere of 80 mL / min, and kept warm for 2 h. The mixture was then naturally cooled to room temperature to obtain a Ru / Zn porous carbon material.
[0073] (5) The product Ru / Zn@NC was transferred into a muffle furnace, heated to 450°C at a heating rate of 5°C / min, kept at this temperature for 5 h, and then naturally cooled to room temperature to obtain the target product of RuO2 / ZnO / Ru / Zn porous carbon.
[0074] (6) OER electrocatalytic performance test: The electrochemical performance test of RuO2 / ZnO / Ru / Zn porous carbon materials was carried out in 1M potassium hydroxide electrolyte at a scan rate of 10 mV / s, with RHE as the reference electrode and an electrochemical window scanning range of 1.2-1.8 V. -2 The corresponding overpotential is 260mV~300mV, among which, the 800℃ sample is 10mA cm -2 The corresponding overpotential is 268mV; 1000℃ sample 10mA cm -2 The corresponding overpotential is 293 mV. Compared with Example 3, the sample calcined at 900°C in a tube furnace (10 mA cm -2 The corresponding overpotential is 253 mV), showing poor electrochemical performance.
[0075] Comparative Example 3:
[0076] Compared with Example 3, most of the steps are the same except that the step of further oxidizing the Ru / Zn porous carbon in air is omitted.
[0077] (1) To prepare ZIF-8 solution, 4.204 g 2-methylimidazole and 1.372 g C4H6O4Zn·2H2O (molar ratio of 4:1) were weighed and dissolved in 30 mL methanol, and magnetic stirring was performed to obtain a fully dissolved solution; the C4H6O4Zn·2H2O methanol solution was slowly added to the 2-methylimidazole methanol solution, and magnetic stirring was performed for 2 h at room temperature until a milky white solution was obtained.
[0078] (2) Hydrothermal preparation of ZIF-8 precursor solution: Pour the milky white solution obtained at room temperature into a polytetrafluoroethylene liner, place it in a high-pressure hydrothermal reactor, heat it to 120°C in an oven, and keep it warm for 4 h;
[0079] (3) Precursor impregnation: Add 260 mg of RuCl3·xH2O (n Zn :n Ru=7.7:1) magnetically stirred for 0.5 h, the brown solution was placed in a beaker and stirred thoroughly, then immersed at room temperature for 24 h; and the mixed solution was placed in a vacuum oven and dried for 12 h.
[0080] (4) Calcination: The crucible containing the dried precursor was placed in a tubular quartz furnace and heated to 900°C at a heating rate of 5°C / min in an argon atmosphere of 80 mL / min, kept warm for 2 h, and then naturally cooled to room temperature to obtain Ru / Zn porous carbon material.
[0081] (5) The product Ru / Zn@NC was not oxidized and directly subjected to OER electrocatalytic performance test: The electrochemical performance test of Ru / Zn porous carbon material was carried out in 1M potassium hydroxide electrolyte with a scan rate of 10 mV / s, RHE as the reference electrode, and an electrochemical window scanning range of 1.2-1.8 V. The 10 mA cm -2 The corresponding overpotential is 540 mV. Compared with Example 3, the sample calcined at 900°C in a tube furnace (the overpotential corresponding to 10 mA cm-2 is 253 mV) exhibits extremely poor electrochemical performance.
[0082] Comparative Example 4:
[0083] Compared with Example 3, most of the above are the same except that no impregnation treatment is used.
[0084] (1) To prepare ZIF-8 solution, 4.204 g 2-methylimidazole and 1.372 g C4H6O4Zn·2H2O (molar ratio of 4:1) were weighed and dissolved in 30 mL methanol, and magnetic stirring was performed to obtain a fully dissolved solution; the C4H6O4Zn·2H2O methanol solution was slowly added to the 2-methylimidazole methanol solution, and magnetic stirring was performed for 2 h at room temperature until a milky white solution was obtained.
[0085] (2) Hydrothermal preparation of ZIF-8 precursor solution: Pour the milky white solution obtained at room temperature into a polytetrafluoroethylene liner, place it in a high-pressure hydrothermal reactor, heat it to 120°C in an oven, and keep it warm for 4 h;
[0086] (3) Calcination: The crucible containing the dried precursor was placed in a tubular quartz furnace, heated to 900°C at a heating rate of 5°C / min in an argon atmosphere of 80 mL / min, kept warm for 2 h, and then naturally cooled to room temperature to obtain a Zn porous carbon material.
[0087] (4) The product Zn@NC was transferred into a muffle furnace, heated to 450°C at a heating rate of 5°C / min, kept at this temperature for 5 h, and then naturally cooled to room temperature to obtain the target product ZnO / Zn porous carbon.
[0088] (5) OER electrocatalytic performance test: The electrochemical performance test of ZnO / Zn porous carbon materials was carried out in 1 M potassium hydroxide electrolyte at a scan rate of 10 mV / s, with RHE as the reference electrode and an electrochemical window scanning range of 1.2-1.8 V. The 10 mA cm -2 The corresponding overpotential is more than 3000 mV. Compared with Example 3, the sample calcined at 900 °C in a tube furnace (10 mA cm -2 The corresponding overpotential is 253mV), which is completely incapable of catalysis.
[0089] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a RuO2 / ZnO / Ru / Zn porous carbon material derived from a ZIFs material, characterized in that: The following steps are involved: (1) slowly adding C4H6O4Zn·2H2O methanol solution into 2-methylimidazole methanol solution, stirring at room temperature until a milky white solution is formed, placing in a high pressure hydrothermal reactor for reaction, and then cooling to room temperature; (2) adding RuCl3·xH2O to the reaction solution cooled in step (1), stirring and mixing to obtain a brown solution, immersing, and drying; (3) placing the dried product obtained in step (2) under an inert atmosphere, heating it for carbonization, and cooling it to obtain Ru / Zn porous carbon; (4) Oxidizing the Ru / Zn porous carbon in an air atmosphere to obtain RuO2 / ZnO / Ru / Zn porous carbon material, which is the target product.
2. The method for preparing a RuO2 / ZnO / Ru / Zn porous carbon material derived from a ZIFs material according to claim 1, characterized in that: In step (1), the molar ratio of 2-methylimidazole to C4H6O4Zn·2H2O is 2-8:
1.
3. The method for preparing a RuO2 / ZnO / Ru / Zn porous carbon material derived from a ZIFs material according to claim 1, characterized in that: In step (1), the reaction temperature is 110-130° C., the reaction time is 4-12 h, and the reaction pressure is 3-8 MPa.
4. The method for preparing a RuO2 / ZnO / Ru / Zn porous carbon material derived from a ZIFs material according to claim 1, characterized in that: In step (2), the addition amount of RuCl3·xH2O and C4H6O4Zn·2H2O satisfies n Zn :n Ru =3.8~7.7:
1.
5. The method for preparing a RuO2 / ZnO / Ru / Zn porous carbon material derived from a ZIFs material according to claim 1, characterized in that: In step (2), the immersion is carried out at room temperature for 18-30 hours.
6. The method for preparing a RuO2 / ZnO / Ru / Zn porous carbon material derived from a ZIFs material according to claim 1, characterized in that: In step (3), the specific process of heating carbonization is: controlling the heating rate to be 2-5°C / min, heating to 800-1000°C, and keeping the temperature for 2-3 hours.
7. The method for preparing a RuO2 / ZnO / Ru / Zn porous carbon material derived from a ZIFs material according to claim 1, characterized in that: In step (4), the specific process of oxidation is: controlling the heating rate to be 2-5°C / min, heating to 450-500°C, and keeping the temperature for 4-6 hours.
8. The method for preparing a RuO2 / ZnO / Ru / Zn porous carbon material derived from a ZIFs material according to claim 1, characterized in that: In step (2), the drying temperature is 80° C. and the drying time is 12 h.
9. A RuO2 / ZnO / Ru / Zn porous carbon material derived from a ZIFs material, which is prepared by the preparation method described in any one of claims 1 to 8.
10. Use of a RuO2 / ZnO / Ru / Zn porous carbon material derived from a ZIFs material as claimed in claim 9 as a catalyst for hydrogen production by water electrolysis, a hydrogen storage material and a chlorine evolution reaction catalyst.
Citation Information
Cited By
Preparation method of nickel felt loaded Ru / ZnO nanoscale layered structure catalyst and product
CN120556088A